The association of rod curvature with postoperative outcomes in patients undergoing posterior lumbar interbody fusion for spinal stenosis: a retrospective case–control study - Lin Han; Hongdao Ma; Qisheng Li; Jincan Yuan; Haisong Yang; Yuchen Qin; Xuhua Lu (BMC Musculoskeletal Disorders, 2023)
Abstract Background Restoration of sagittal balance is a crucial consideration in posterior lumbar interbody fusion (PLIF) surgery and adverse postoperative outcomes are associated with inadequate restoration of sagittal alignment. However, there remains a shortage of substantial evidence regarding the effect of rod curvature on both sagittal spinopelvic radiographic parameters and clinical outcomes. Method A retrospective case–control study was conducted in this study. Patient demographics (age, gender, height, weight and BMI), surgical characteristics (number of fused levels, surgical time, blood loss and hospital stay) and radiographic parameters (lumbar lordosis [LL], sacral slope [SS], pelvic incidence [PI], pelvic tilt [PT], PI-LL, Cobb angle of fused segments [Cobb], rod curvature [RC], Posterior tangent angle of fused segments [PTA] and RC-PTA) were analyzed. Results Patients in the abnormal group had older mean age and suffered more blood loss than those in the normal group. In addition, RC and RC-PTA were significantly lower in the abnormal group compared to the normal group. Multivariate regression analysis revealed that lower age (OR = 0.94; 95% CI: 0.89–0.99; P = 0.0187), lower PTA (OR = 0.91; 95% CI: 0.85–0.96; P = 0.0015) and higher RC (OR = 1.35; 95% CI: 1.20–1.51; P < 0.0001) were related to higher odds of better surgical outcomes. The receiver operating characteristic curve analysis showed that the ROC curve (AUC) for predicting outcomes of surgery by RC classifier was 0.851 (0.769–0.932). Conclusions In patients who underwent PLIF surgery for lumbar spinal stenosis, those who had a satisfactory postoperative outcome tended to be younger, had lower blood loss, and higher values of RC and RC-PTA compared to those who had poor recovery and required revision surgery. Additionally, RC was found to be a reliable predictor of postoperative outcomes.